Control of the Purity of 93% Oxygen Obtained from the Air by Pressure Swing Adsorption - R. A. Enikeeva; Yu. V. Miroshnichenko; V. L. Bagirova; O. A. Popova (Регуляторные исследования и экспертиза лекарственных средств)
The assessment of the quality of 93% oxygen obtained from the air by pressure swing adsorption (PSA) presents an important challenge for applied research. Such an assessment provides a possibility to guarantee the safety of oxygen therapy using both stationary and portable PSA-based oxygen concentrators. In this article, the experts of the Scientific Centre for Expert Evaluation of Medicinal Products and S.M. Kirov Military Medical Academy offer their recommendations for the implementation of monograph 2.2.0037.22 Oxygen (93 per cent) in civil healthcare organisations or military medical units. The publication of this monograph, which was approved by order No. 126 issued by the Ministry of Health of the Russian Federation on 01.03.2022, became the endpoint of the experts’ cooperation aimed at the inclusion of 93% oxygen into the Russian State Register of Medicinal Products.